IMPLEMENTASI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN MATEMATIKA KELAS IV PADA MATERI APROKSIMASI DI SDS TARBIYATUL ISLAM SAMBAS TAHUN PELAJARAN 2024-2025 - Nurul Chaniago; Yusrain Yusrain; Sera Yuliantini (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The purpose of this study is to reveal about: 1) Planning a contextual approach to learning mathematics in grade IV on approximation materials at SDS Tarbiyatul Islam Sambas for the 2024-2025 Academic Year; 2) Implementation of a contextual approach to grade IV mathematics learning on approximation materials at SDS Tarbiyatul Islam Sambas for the 2024-2025 Academic Year; 3) The results of the implementation of a contextual approach to grade IV mathematics learning on approximation materials at SDS Tarbiyatul Islam Sambas for the 2024- 2025 Academic Year. This study uses a qualitative approach with a type of phenomenological research. Data collection techniques use interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of the study show that; 1) Planning a contextual approach to learning mathematics in grade IV on approximation materials at SDS Tarbiyatul Islam Sambas for the 2024-2025 Academic Year, namely, at SDS Tarbiyatul Islam Sambas, the development of approximation teaching materials using a contextual approach has succeeded in increasing students' interest, but faces challenges in ensuring varied understanding and time constraints. 2) The implementation of a contextual approach to grade IV mathematics learning on approximation material at SDS Tarbiyatul Islam Sambas for the 2024- 2025 Academic Year, namely, teachers design approximation learning with a contextual approach that relates mathematical concepts to daily life, but challenges arise in students' varied understanding and time constraints. To increase engagement, group discussions, practical assignments, and props adapted to students' abilities are used, and evaluations are carried out through practice, observation, and reflection. 3) The results of the implementation of the contextual approach to grade IV mathematics learning on approximation material at SDS Tarbiyatul Islam Sambas for the 2024- 2025 Academic Year, namely, The contextual approach at SDS Tarbiyatul Islam Sambas is effective in increasing the understanding of the concept of approximation, problem-solving skills, motivation, student involvement, and collaborative skills, with evaluation results showing a positive increase.